Retromer in Osteoblasts Interacts With Protein Phosphatase 1 Regulator Subunit 14C, Terminates Parathyroid Hormone's Signaling, and Promotes Its Catabolic Response - Lei Xiong; Wen-Fang Xia; Fu-Lei Tang; Jin-Xiu Pan; Lin Mei; Wen-Cheng Xiong (EBioMedicine, 2016)
Parathyroid hormone (PTH) plays critical, but distinct, roles in bone remodeling, including bone formation (anabolic response) and resorption (catabolic response). Although its signaling and function have been extensively investigated, it just began to be understood how distinct functions are induced by PTH activating a common receptor, the PTH type 1 receptor (PTH1R), and how PTH1R signaling is terminated. Here, we provide evidence for vacuolar protein sorting 35 (VPS35), a major component of retromer, in regulating PTH1R trafficking, turning off PTH signaling, and promoting its catabolic function. VPS35 is expressed in osteoblast (OB)-lineage cells. VPS35-deficiency in OBs impaired PTH(1–34)-promoted PTH1R translocation to the trans-Golgi network, enhanced PTH(1–34)-driven signaling, and reduced PTH(1–34)'s catabolic response in culture and in mice. Further mechanical studies revealed that VPS35 interacts with not only PTH1R, but also protein phosphatase 1 regulatory subunit 14C (PPP1R14C), an inhibitory subunit of PP1 phosphatase. PPP1R14C also interacts with PTH1R, which is necessary for the increased endosomal PTH1R signaling and decreased PTH(1–34)'s catabolic response in VPS35-deficient OB-lineage cells. Taken together, these results suggest that VPS35 deregulates PTH1R-signaling likely by its interaction with PTH1R and PPP1R14C. This event is critical for the control of PTH(1–34)-signaling dynamics, which may underlie PTH-induced catabolic response and adequate bone remodeling.